The Effect of Domestic Waste on Mollusca Diversity and Their Role in the Ecosystem of the Mangrove Area in Tarakan, North Kalimantan - Nugroho, Bimo Aji; Putri, Erisa Ayu Waspadi; Abrori, Fadhlan Muchlas (Universitas Negeri Surabaya, 2025)
Mangroves are vital ecosystems for biodiversity, but are increasingly threatened by pollution, especially domestic waste. This study focuses on the impact of domestic pollution on the diversity of Mollusca on Tarakan Island, North Kalimantan. Although several studies have examined molluscan diversity, there is a lack of analysis of the direct impact of pollution on these species. The method used was belt transects to measure species diversity, dominance and distribution of Mollusca in 4 habitats. The results were conducted in four mangrove habitats, and 36 species of Mollusca, 32 species of gastropods, and four species of Bivalvia were identified. The results showed that habitat 1, with the lowest level of pollution, had the most stable community index, while the habitat with the highest level of pollution showed a significant decline based on the community index. These findings confirm the importance of protecting mangrove ecosystems to maintain Bivalvia diversity and provide a basis for better environmental management policies. This research also opens opportunities for further studies on the interaction between pollution and biodiversity in mangrove ecosystems.